2010
DOI: 10.1364/ol.35.001341
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy of bismuth-doped pure silica fiber preform

Abstract: We report on the optical spectroscopy of monolithic fiber preform prepared from nanoporous bismuth-doped silica glass. The experiments reveal the existence of at least two different types of active centers and clearly demonstrate that the presence in the glass matrix of other dopant is not necessary to obtain the near-IR photoluminescence connected to Bismuth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 13 publications
2
42
2
Order By: Relevance
“…In a first consideration, probably not noted by Kustov et al, the pair Bi-Ta does not follow the rule, although NIR emission has been observed for this case, as well [17]. Also in some other cases [16], NIR emission can be found even when no co-dopant is present in the host, as for instance in the very recent result on Bi-doped pure SiO 2 [52].…”
Section: Intramolecular Charge Transfer (Ict) Model For Bi 5+ O N 2− mentioning
confidence: 58%
“…In a first consideration, probably not noted by Kustov et al, the pair Bi-Ta does not follow the rule, although NIR emission has been observed for this case, as well [17]. Also in some other cases [16], NIR emission can be found even when no co-dopant is present in the host, as for instance in the very recent result on Bi-doped pure SiO 2 [52].…”
Section: Intramolecular Charge Transfer (Ict) Model For Bi 5+ O N 2− mentioning
confidence: 58%
“…1c. The relaxation process of photoluminescence in bismuth-doped fiber frequently exhibits bi-exponential decay1314. The fast recovery component typically varies from hundreds of nanoseconds to a few microseconds, depending on fiber core composition, while the slow recovery factor was found to be around ~ 700 µs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it seems that several different emitters contribute to the net NIR photoluminescence in Bi-doped SiO 2 and GeO 2 -based glasses. 37,38 To understand the origin of NIR photoluminescence in Bi-containing silicate and germanate glasses, the investigation of model SiO 2 or GeO 2 -based crystals doped with bismuth is highly desirable, since crystal hosts offer a more restrictive and structured environment for the possible bismuth-containing luminescent species. This aspect can diminish the diversity of possible luminescent centers, simplifying the interpretation of photoluminescence spectra.…”
Section: Introductionmentioning
confidence: 99%